2022
DOI: 10.1186/s12877-022-03013-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of food neophobia and oral health on the nutritional status of community-dwelling older adults

Abstract: Background Food preferences and oral health of older adults greatly affect their nutritional intake, and old-age–related increase in food neophobia may consequently reduce food intake in older adults. This study aimed to determine the impact of food neophobia and oral health on nutritional risk in community-dwelling older adults. Methods This cross-sectional study included 238 independent adults aged ≥ 65 years (mean, 76.3 ± 7.3 years). The survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…After publication of this article [ 1 ], the authors reported that in this article the author name Miki Marutani was incorrectly written as Mika Marutani.…”
mentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in this article the author name Miki Marutani was incorrectly written as Mika Marutani.…”
mentioning
confidence: 99%